Multipurpose Energy Saving Manual Compressor for Artisans in African Countries - Dr. Isaac Ali Kwasu; Dr. Aje Tokan; Engr. M A Bawa (International Journal of Engineering and Management Research, 2018)
This Research work involves the design, fabrication and testing of a manually operated compressor for use of artisans and small scale vulcanizing activities. The developed machine consists of chain sprocket arrangement to a flywheel attached to a pulley which powers the compressor as well as a storage tank to receive air by foot pedaling. The article is an innovative product to meet the needs of rural African Artisans that uses air compressor for their daily activities . The design is such that the chain sprocket provides the compressor with a driving force in conjunction with the flywheel thereby replacing the prime mover. Prototype pilot test carried out on the developed manual air compressor could generates 10 Psi ie 0.69bar-volume of air in 60 seconds. A new design with better parameter of the machine was done to improve it’s proficiency after testing for broad application even for the handicap Artisans.